2018
DOI: 10.1002/biof.1429
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α‐cyclodextrin modifies gut microbiota and reduces fat accumulation in high‐fat‐diet‐fed obese mice

Abstract: We investigated the effect of α-cyclodextrin (α-CD) on the bacterial populations of gut microbiota, production of organic acids, and short-chain fatty acids (SCFAs), and lipid metabolism in obese mice induced by feeding a high-fat diet (HFD). Male C57BL/6J mice were assigned to three diet groups: normal diet (ND) (5% [w/w] fat), HFD (35% [w/w] fat), and HFD (35% [w/w] fat) + 5.5% (w/w) α-CD for 16 weeks. Increases in body and epididymal adipose tissue weights were observed in the HFD group compared with the ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 53 publications
2
31
0
2
Order By: Relevance
“…It has previously been shown that aCD prevented the body weight gain and reduced atherogenic lipoproteins in human and rats. (13,14,35,36) Nihei et al (29) have reported that 5.5% aCD treatment reduced body weight gain and epididymal fat weight in mice fed HFD [35% (w/w) fat]. Because of its interaction with lecithin precipitation, aCD decreased the micellar cholesterol solubility of dietary fat in intestinal fluid and prevented the absorption of cholesterol in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that aCD prevented the body weight gain and reduced atherogenic lipoproteins in human and rats. (13,14,35,36) Nihei et al (29) have reported that 5.5% aCD treatment reduced body weight gain and epididymal fat weight in mice fed HFD [35% (w/w) fat]. Because of its interaction with lecithin precipitation, aCD decreased the micellar cholesterol solubility of dietary fat in intestinal fluid and prevented the absorption of cholesterol in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between our results and those of the previous study may be attributable to the differences in the dose of aCD, diet components, or the type of fat used in the experimental diet. (29) At the molecular level, AITC suppresses the production of Tnf-a by inhibiting the activation of macrophages in adipose tissue. (39) In another study, MTBI was shown to exert a chemoprotective effect, attributed to its antioxidant activity, which is higher than that of vitamins C and E. (40) Oxidative stress is regulated by the balance between the ROS production and the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The food-grade flaxseed lignans used in this experiment contained approximately 40% (w w -1 ) α-cyclodextrin as an inclusion compound. Alpha-cyclodextrin, a member of the cyclic oligosaccharide family composed of six glucose subunits, was reported to change the gut microbiota and reduce weight gain of epididymal adipose tissue in mice fed with a high-fat diet 20 . We therefore similarly examined the activity of α-cyclodextrin.…”
Section: Administration Of α-Cyclodextrin Increased B Uniformis Cellmentioning
confidence: 99%
“…During exercise, subjects maintained a pedal speed of 60 rpm. RPE was measured with the Borg scale at baseline and at 10,20,30,40,45, and 50 min of exercise. In addition, a VAS questionnaire was used to assess fatigue after exercise testing (0, 30, 60 min).…”
Section: Human Study With Flaxseed Lignan or α-Cyclodextrin As Test Fmentioning
confidence: 99%